Lessons from defeat: an analysis of two newsgames from Argentina abstract. - Mancuso, Mariano (2023)
At the beginning of the new millennium, video games started establishing links with other fields of culture, such as art, advertisement, politics and activism, among others. The combination with journalism gave rise to newsgame, a form of video game that follows the rules of the field of information, such as the coverage of current events and the creation of an agenda. The change of operation caused transformations: for example, failure, instead of being a disadvantage, enabled different ways of questioning news. This paper analyzes two newsgames from the Argentinean studio Shitty Games. Considering former elements of video game, especially from the 8-bit period, but operating within the field of journalism, Decretator (2016) and Suicid.ar (2015) refer to two recent events in Argentina and editorialize them using argumentative strategies of persuasion, typical of the persuasive genres of journalism (such as the editorial or the opinion article). Moreover, they provide a polemical space that invites users to take a stance on the government layoffs carried out by the government of Mauricio Macri and on the coverage by different media regarding the death of prosecutor Alberto Nisman.